CLASS MANAGEMENT IN INCREASING STUDENTS' INTEREST IN LEARNING IN MADRASAH IBTIDAIYAH NEGERI 1 CITY OF JAMBI - Atika Atika (International Journal of Southeast Asia, 2021)
School is an institution where a student studies formally and is a forum for students to determine the direction or steps they want to take and to determine the goals they want to achieve for their future. School is the second place after home for students to study. At school, students will exchange ideas with colleagues and receive good attention from educators (teachers). Educational activities in schools are always related to human development efforts, so the success of education is very dependent on the human element. Because the human element determines the success or failure of education. One of the human elements that determine the quality of education is the teaching staff. The personality of the educator is a measure of the personality formation of students in education. Educators must be able to be role models that should be followed by their students at school as figures who have good personalities.